The 5 love languages : the secret to love that lasts - Chapman, Gary D., 1938- (Chicago : Northfield Pub., 2010)
Dr. Chapman explains how people communicate love in different ways, and shares the wonderful things that happen when men and women learn to speak each other's language.
What happens to love after the wedding? -- Keeping the love tank full -- Falling in love -- Love language #1: words of affirmation -- Love language #2: quality time -- Love language #3: receiving gifts -- Love language #4: acts of service -- Love language #5: physical touch -- Discovering your primary love language -- Love is a choice -- Love makes the difference -- Loving the unlovely -- A personal word -- Frequently asked questions -- The five love languages profile for husbands -- The five love languages profile for wives.
Includes bibliographical references.
Keywords: Marriage; Communication in marriage; Love